2000
DOI: 10.1117/12.386875
|View full text |Cite
|
Sign up to set email alerts
|

<title>WDM/TDM optical-packet-switched network for supercomputing</title>

Abstract: A new optical packet switching network and its enabling technologies are investigated for implementation in a Petaflops scale supercomputer system. We capitalize on the immense bandwidth of the optical fiber interconnects by deploying WDM/TDM packet payloads. To accommodate current optical switching technologies, the routing operations in the network are drastically simplified and the need for buffering is completely eliminated. This paper presents the experimental demonstration of the routing within the uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…To experimentally demonstrate the routing functions of the data-vortex switch and measure the physical layer performance, we constructed a routing-node test bed [15], [16]. The test bed is configured in a recirculating loop fashion to emulate packets propagating through multiple node hops.…”
Section: Experimental Test Bedmentioning
confidence: 99%
“…To experimentally demonstrate the routing functions of the data-vortex switch and measure the physical layer performance, we constructed a routing-node test bed [15], [16]. The test bed is configured in a recirculating loop fashion to emulate packets propagating through multiple node hops.…”
Section: Experimental Test Bedmentioning
confidence: 99%
“…4), that emulates routings under cascaded node hops [3], [4]. In this experiment, another node (labeled node 1 in Fig.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The switch fabric size is characterized by two parameters and , representing the number of nodes along the angle and height dimensions, respectively. is typically set to be a small odd number ( 10), and is independent of the choice of . The available number of input/output (I/O) ports is given by .…”
Section: Architecture Overviewmentioning
confidence: 99%
“…Using DWDM within the data payloads further enhances high data throughput. In previous work, we have investigated the basic routing functionality, control signaling mechanism, and wavelength routing technique within an experimental test bed [9], [10]. In addition, our simulation results have shown that the Data Vortex packet switch achieves high scalability, low latency, and narrow latency distribution under uniform and random traffic conditions [11].…”
Section: Introductionmentioning
confidence: 98%